2020
DOI: 10.1080/22243534.2020.1869456
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on hospitality industry trade unionism in the UK and beyond

Abstract: The study of traditional industrial relations institutions in the hospitality industry (such as trade unions) is somewhat in the doldrums. This is, perhaps, unsurprising, given that the sector has historically never had high union membership. This article briefly explores the general influence of trade unions today in terms of overall membership and the concept of union density. The observed decline in the numerical (membership) strength of unions and their influence is clearly attributable to the -albeit unev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Plus, it has been argued that the hospitality sector's employment precarity is prevalent worldwide (Robinson et al, 2019), including Europe (e.g., Kearsey, 2020; McKay et al, 2012) with a workforce of high heterogeneity (Bolton et al, 2018) and job insecurity even amongst people holding permanent jobs in this industry (McNamara et al, 2011)—offering our results significant relevance to European management scholarship and practice. Thus, given the types of workers studied in this research, we surmise that similar effects would apply throughout regions such as the European Union, given the heavy reliance on variable labour in the hospitality industry and other industries (Wood, 2020). For instance, owing to the consequences of the COVID‐19 pandemic, many European labour migrants in hospitality have lost their jobs in the host country and returned home, in some instances forcibly—leading to more pressure on job markets and intense competition in areas of return with resident workers (ILO, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…Plus, it has been argued that the hospitality sector's employment precarity is prevalent worldwide (Robinson et al, 2019), including Europe (e.g., Kearsey, 2020; McKay et al, 2012) with a workforce of high heterogeneity (Bolton et al, 2018) and job insecurity even amongst people holding permanent jobs in this industry (McNamara et al, 2011)—offering our results significant relevance to European management scholarship and practice. Thus, given the types of workers studied in this research, we surmise that similar effects would apply throughout regions such as the European Union, given the heavy reliance on variable labour in the hospitality industry and other industries (Wood, 2020). For instance, owing to the consequences of the COVID‐19 pandemic, many European labour migrants in hospitality have lost their jobs in the host country and returned home, in some instances forcibly—leading to more pressure on job markets and intense competition in areas of return with resident workers (ILO, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…These scholars found that unions possess the power to represent and protect their member interests in the workplace. Lastly, poor collaboration between employers and employees exists (Arslanov and Safin, 2016;Wood, 2020). Contrarily, Cook et al (2020) found that cooperation and collaboration between management and employees prevail.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, ‘hotel and catering workers to some extent assume the values of their social superiors (managers and guests), values which are highly individualistic and hostile to trade unionism’ (Aslan & Wood, 1993, p. 61). What is more, the hostile attitude to unionisation of employers and managers does not help (Wood, 2020). It follows that increasing unionisation rates in the hotel calls for deep and sustained engagement on the part of union leaders, in both Poland and other developed economies.…”
Section: Context Of the Studymentioning
confidence: 99%
“…This study contributes to the literature on hotel employees' well‐being and the attractiveness of hotel employment (e.g., Ariza‐Montes et al, 2018; Ashton, 2018; Su & Swanson, 2019; Yavas et al, 2018) in the wider context of organisational ethics (Greenwood, 2013). At the same time, it makes contributions to the body of research on collective representation in the hotel industry, which draws mainly on evidence from Anglo‐Saxon countries (Aslan & Wood, 1993; Ioannou & Dukes, 2021; Lowery et al, 2019; Macaulay & Wood, 1992; Piso, 2003; Wood, 2020). To the best of our knowledge, there are no many studies focusing on unionisation in Polish hotels.…”
Section: Introductionmentioning
confidence: 99%